Strongly (E,F)-convexity with applications to optimization problems - Enad, Ammar A.; Majeed, Saba N. (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2019)
In this paper, a new class of nonconvex sets and functions called strongly -convex sets and strongly -convex functions are introduced. This class is considered as a natural extension of strongly -convex sets and functions introduced in the literature. Some basic and differentiability properties related to strongly -convex functions are discussed. As an application to optimization problems, some optimality properties of constrained optimization problems are proved. In these optimization problems, either the objective function or the inequality constraints functions are strongly -convex.